Composing for Japanese instruments - Miki, Minoru 1930-2011 (Boydell & Brewer, 2008)
The unique sounds of the biwa, shamisen, and other traditional instruments from Japan are heard more and more often in works for the concert hall and opera house. Composing for Japanese Instruments is a practical orchestration/instrumentation manual with contextual and relevant historical information for composers who wish to learn how to compose for traditional Japanese instruments. Widelyregarded as the authoritative text on the subject in Japan and China, it contains hundreds of musical examples, diagrams, photographs, and fingering charts, and comes complete with two accompanying compact discs of musical examples. Its author, Minoru Miki, is a composer of international renown and is recognized in Japan as a pioneer in writing for Japanese traditional instruments. The book contains valuable appendices, one of works Miki himself has composed using Japanese traditional instruments, and one of works by other composers -- including Toru Takemitsu and Henry Cowell -- using Japanese traditional instruments. Marty Regan is Assistant Professor of Music at Texas A&M University; Philip Flavin is a Research Fellow in the School of Languages, Cultures and Linguistics at Monash University, Australia
Title from publisher's bibliographic system (viewed on 29 Sep 2017)
Wind instruments -- String instruments (lutes) -- String instruments (zithers) -- Percussion instruments
Title from publisher's bibliographic system (viewed on 29 Sep 2017)
Wind instruments -- String instruments (lutes) -- String instruments (zithers) -- Percussion instruments
Keywords: Composition (Music); Musical instruments / Japan; Komposition -- Musik; Musikinstrument; Japan